I giovani maoresi e la mobilità. La sfida dell’istruzione tra vecchie e nuove disuguaglianze - Paola Schierano (Archivio Antropologico Mediterraneo)
Mobility constitutes a dynamic force of most European overseas areas, including non-independent regions, countries and territories, integrated or associated with a member state of the European Union. Despite financial efforts and cohesion plans to reduce the structural backwardness, Europeans citizens living in the Overseas areas are often obliged to move to the “continent” to benefit from better social and economic opportunities at both educational and professional levels. EU overseas students represent the most travelling group, among them, young people from Mayotte (French Overseas Department of the Indian Ocean) stand out: more than half of them reside in metropolitan France and, to a lesser extent, in La Réunion island. By interweaving ethnographic experience and in-depth historical analysis, this article offers a contribution to a wider reflection on youth and inequalities, looking at the gap between centres and (ultra)peripheral regions. It analyses the educational system of Mayotte, characterized by the integration of republican school and Koranic school, as well as factors and limitations to Mahoran students’ mobility. The aim of this essay is to show how unequal policies, a legacy from the colonial past, reverberate in the present of Mahoran people, deeply conditioning it at migratory, educational and professional level. The exploration concludes with a brief overview of the effects of the first wave of the Covid-19 pandemic on Mahoran students in the diaspora, too often subjected to isolation, discrimination and school dropout.